Medical pre-operative considerations for patients undergoing penile implantation - Masterson, Thomas A.; Palmer, Joseph; Dubin, Justin; Ramasamy, Ranjith (Translational Andrology and Urology, 2017)
Penile prosthesis surgery has become the standard treatment for patients with erectile dysfunction refractory to medical management. Refinements in the both the surgical technique and device manufacturing have made this a safe and reliable treatment with excellent patient satisfaction. In this review, we will overview the basic medical and pre-operative considerations for patients undergoing penile prosthesis implantation. We intend to provide a simple and practical checklist for the implanter to reference when considering implantation of a penile prosthesis.